Elective neck dissection during salvage laryngectomy: A systematic review and meta‐analysis. (8th October 2019) - Gross, Jennifer H.; Vila, Peter M.; Simon, Laura; Rizvi, Zain H.; Zenga, Joseph; Jackson, Ryan S.; Pipkorn, Patrik
Abstract : Objectives: The primary objective was to determine the rate of occult cervical nodal metastasis in patients undergoing elective neck dissection (END) during salvage laryngectomy. The secondary objective was to compare survival and postoperative complication rates between patients undergoing END versus observation. Methods: A medical librarian performed a comprehensive search for END outcomes in laryngeal cancer patients undergoing salvage laryngectomy after primary chemoradiation therapy. Seventeen retrospective studies and 1 prospective study met inclusion criteria, with a total of 1, 141 patients (799 END, 350 observed). Results: The rate of nodal positivity was 11% among patients who underwent END during their salvage laryngectomy. Three studies and 155 patients were included in a 5‐year overall survival (OS) analysis with no significant difference in OS (95% confidence interval [CI]: 0.82‐2.22). After inclusion of six studies and 494 patients (249 END, 245 observed), the risk of fistula formation was not statistically different (95% CI: 0.61‐2.56). Due to significant heterogeneity between studies and inadequate data, most patients could not be included in the meta‐analysis of outcomes. Conclusion: Salvage laryngectomy patients undergoing END have an occult nodal positivity rate of 11%. Meta‐analysis showed no statistically significant differences in 5‐year OS between patients undergoing END versus observation. Laryngoscope, 130:899–906, 2020